2018
DOI: 10.1037/cdp0000218
|View full text |Cite
|
Sign up to set email alerts
|

Acute salivary cortisol response among Mexican American adolescents in immigrant families.

Abstract: The study demonstrates that the modified TSST task can elicit an acute hypothalamic-pituitary-adrenal axis response, but the nature of this response is dependent upon participants' perceptions of language brokering (parental dependence and efficacy), parental hostility, and discrimination experiences. Adolescents' individual characteristics and contextual demands remain important considerations in understanding their acute stress responses. (PsycINFO Database Record (c) 2018 APA, all rights reserved).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…In accordance with the IRR model, cultural constructs manifested at several contextual levels. Cultural factors as operationalized at the individual (e.g., Zeiders et al., 2018), microsystems (e.g., Kim, Zhang, et al, 2018), and sociopolitical (Zeiders et al., 2019) levels showed associations with stress biology. Many of these studies found direct relationships between certain cultural constructs and measures of stress biology (Doan et al., 2017; Doane et al., 2018; Gonzales, Knight, et al, 2018; Zeiders et al., 2018), while other studies found no such associations (Luecken et al., 2013, 2015; Waters et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the IRR model, cultural constructs manifested at several contextual levels. Cultural factors as operationalized at the individual (e.g., Zeiders et al., 2018), microsystems (e.g., Kim, Zhang, et al, 2018), and sociopolitical (Zeiders et al., 2019) levels showed associations with stress biology. Many of these studies found direct relationships between certain cultural constructs and measures of stress biology (Doan et al., 2017; Doane et al., 2018; Gonzales, Knight, et al, 2018; Zeiders et al., 2018), while other studies found no such associations (Luecken et al., 2013, 2015; Waters et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mexican-American adolescents' cortisol reactivity to a task involving translation of a medical document for their parents (Kim, Zhang, Zhang, Zeiders, Sim, & Gleason, 2018). This task did indeed evoke a significant cortisol response, but the magnitude of this response between cultural values and waking and diurnal cortisol activity (Sladek, Doane, Gonzales, Grimm, & Luecken, 2019).…”
Section: Adolescence (12 To 19 Years)mentioning
confidence: 90%
See 1 more Smart Citation
“…More importantly, future research may explore how the language broker role identity ties in with other aspects of Latinx adolescents' social identities to improve adolescents' overall well-being. In addition, language brokering has been shown to be related to adolescents' emotional adjustment (Martinez, McClure, & Eddy, 2009) and physiological health (Kim, Zhang, Zeiders, Sim, & Gleason, 2018). Future studies may build upon the current work and investigate the links between language broker role identity and other significant identity outcomes and critical psychosocial correlates to promote greater understanding of the development of ethnic minority adolescents from immigrant families.…”
Section: Discussionmentioning
confidence: 85%
“…One suggestion is for policy makers and individuals who work directly with immigrant families to provide professional translation services with regard to particularly challenging translation tasks (e.g., brokering in medical contexts). There is qualitative, quantitative, and physiological evidence that suggests that brokering in medical contexts can be particularly stressful for young brokers (Corona et al, 2012), causing acute stress response (Kim, Zhang, Zeiders, Sim, & Gleason, 2018) and leading to psychological problems in the young brokers (Anguiano, 2018). However, it is important to note that the language brokering practice per se is not necessarily a risk factor and can even confer benefits to brokers’ well-being if practiced in a low-stress context (Anguiano, 2018).…”
Section: Discussionmentioning
confidence: 99%